Shamans and “Dark Agencies”: War, Magical Parasitism, and Re-Enchanted Spirits in Siberia - Konstantinos Zorbas (Religions, 2024)
Alleged practices of magical assault and vampirism are a recurrent feature of popular explanations of misfortune in Tuva, South Siberia. Based on a field study of healing practices in an “Association of Shamans”, this article analyses rituals of redressing curse afflictions in the context of Russian political domination. A central purpose of this discussion is to foreground the centrality of kinds of parasitical worship and occult threat to structures of political power in—and beyond—the territory of Tuva. Focusing on a “cursescape”, which develops from the combative practices of shamans, occult specialists, and office-holders, the article probes a repertoire of shamanic healing symbols. It is argued that healing efficacy is constructed in the process of engaging with hunting symbols and animal spirits, which appear in Indigenous Siberian cosmologies. The analysis shows that ideas of ritual risk underpin the process of symbolic resolution. Whereas shamanic practices provide refuge to spirits evicted from their natural landscapes, Tibetan Buddhism—the unifying religion of Tuva—offers an alternative path of healing the effects of the shamans’ propagation of spirits. The article highlights indigenous perceptions of a “cursed” landscape as a space where the agencies of “darkness” and their political sponsors are confronted with an emancipating religious modality emerging from local Buddhist rituals. The analysis displays the unsolved drama of itinerant spirits and shamanic ancestral souls, whose agency is revealed through successive—yet inauspicious—forms of reincarnation.